Analisis Kapitalisme Max Weber sebagai Jalan Pendidikan Agama Kristen Menghadapi Kemiskinan - Boy Anto Ando Silitonga; Jefrit Johanis Messakh; Lamhot Naibaho; Djoys Anneke Rantung (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2023)
This study explores the application of Max Weber's seminal work, Protestant Ethics and the Spirit of Capitalism, as a basis for Christian religious education to effectively address the issue of poverty in modern society. By examining the historical context and underlying principles, the author suggests how Christian religious education can use Weber's ideas to promote critical understanding of economic issues and empower people to participate in overcoming poverty. The method used is a literature study approach, where the author collects data from books and relevant topics or issues in this research. The results of this study seek to bridge Weber's sociological insights with the teachings of Christian religious education, by looking at how the principles of hard work, discipline, and individual responsibility can be instilled through the lens of Christian religious education to empower communities in the fight against poverty. By instilling values that promote economic empowerment, community development, and social responsibility, Christian religious education emerges as a powerful tool to address the challenges of poverty in contemporary society.